A Precise Definition of the Term “Corporate Social Costs”: An Initiative to Enrich the Thought of Accounting for CSR - Younis A. Battal Saleh (FEB-Telkom University Publisher, 2025)
Purpose: This study aims to develop a precise definition of the term